Co-infection of two Ganoderma boninense strains on oil palm seedlings - Rahmad Fadli; Suwandi Suwandi; Nurhayati Damiri (Universitas Lancang Kuning, 2022)
Ganoderma boninense is the basal stem rot disease (BSR) pathogen that devastates oil palm plantations. Disease infection generally occurs by a single strain of G. boninense, or co-infection of two strains arises as revealed by somatic incompatibility. This study aimed to determine the effects of co-infection of two somatically incompatible G. boninense strains on the BSR disease of oil palm seedlings. Two strains of G. boninense were from 2 oil palm plantations and had different aggressiveness. Co-infection of two G. boninense strains was performed by inoculating the Ganoderma rubber wood blocks to the 3-month-old oil palm seedling and examined for 7 months. The results showed that co-infection with two G. boninense strains had similar disease symptoms, decreased disease severity (score 1.5 compared to 2.0 for a single aggressive strain), and similar seedling growth retardation by the single aggressive strain. Higher fungal colonization (92%) of oil palm roots was exhibited in the co-infection compared to 85‒86% colonization of a single strain infection. This study revealed that co-infection with two somatically incompatible strains might favor host colonization by G. boninense.